Subtitling Arabic dialogues in Netflix’s The Crown into English: treatment of cultural challenges - Linda S. Al-Abbas (Cogent Arts & Humanities)
This study examined the translation strategies used in subtitling Arabic dialogues in Netflix’s The Crown into English with specific reference to idioms, slang expressions, and offensive language and taboos. The data, which included Arabic examples of the specified categories along with their English subtitles, were collected and qualitatively analyzed according to different typologies of equivalence proposed by previous studies, including those by Vinay and Darbelnet (2004), Baker (1992) and Díaz Cintas and Remael (2021). The findings revealed that in translating idioms, paraphrasing was the most utilized strategy that successfully delivered the literal meaning but fell short of capturing the negative connotations of the expressions. For slang expressions, the subtitler opted for omission and using equivalents with less expressive meanings. When translating offensive language and taboos, the expressions were either softened or omitted to minimize their negative impact on the audience, especially those concerning British royalty. Expressions related to non-royals, however, were translated literally. This study can help subtitlers and translation students enhance their skills in rendering culture-specific expressions, including idiomatic, slang, and offensive expressions. It is recommended that translators strike a balance between adapting expressions to resonate with the target audience while maintaining the authenticity of the original dialogue.